Selling tours: the point where it is profitable for both tour operators and clients - Olimovich, Rakhimov Sardor (PT. Antis International Publisher, 2024)
Selling tours is beneficial for both parties - tour operators and clients, providing the opportunity to gain access to a variety of travel offers and save on travel